African-specific polymorphisms in Plasmodium falciparum serine repeat antigen 5 in Uganda and Burkina Faso clinical samples do not interfere with antibody response to BK-SE36 vaccination - Arisue, Nobuko; Palacpac, Nirianne Marie Q.; Ntege, Edward H.; Yeka, Adoke; Balikagala, Betty; Kanoi, Bernard N.; Bougouma, Edith Christiane; Tiono, Alfred B.; Nebie, Issa; Diarra, Amidou; Houard, Sophie; D'Alessio, Flavia; et al. (Frontiers in Cellular and Infection Microbiology, 2022)
BK-SE36, based on Plasmodium falciparum serine repeat antigen 5 (SERA5), is a blood-stage malaria vaccine candidate currently being evaluated in clinical trials. Phase 1 trials in Uganda and Burkina Faso have demonstrated promising safety and immunogenicity profiles. However, the genetic diversity of sera5 in Africa and the role of allele/variant-specific immunity remain a major concern. Here, sequence analyses were done on 226 strains collected from the two clinical trial/follow-up studies and 88 strains from two cross-sectional studies in Africa. Compared to other highly polymorphic vaccine candidate antigens, polymorphisms in sera5 were largely confined to the repeat regions of the gene. Results also confirmed a SERA5 consensus sequence with African-specific polymorphisms.
Gesehen am 21.02.2023